Clinical case of 65 year-old patient with arthralgia and abdominal pain - A. F. Sheptulina; V. T. Ivashkin; T. P. Nekrasova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of the publication. The «Clinical discussion» section will present clinical cases of the Vasilenko Clinic of internal diseases propedeutics, gastroenterology and hepatology, Sechenov First Moscow state medical university. Each clinical case is accompanied by the comments reflecting stepwise differential diagnostic approach. The section is opened by clinical case of the patient with systemic disease and multiply organ involvement.